Capabilities and actors in erp systems management: an exploratory study in corporate users of SAP ERP (Journal of Information Systems and Technology Management, 2007)
ERP systems are now an important component of information technology architecture in most large and medium sized companies. As such, it is inevitable that the activities undertaken to align this component to business requirements, conduct its evolution and ensure its performance and availability become increasingly important to companies' IT areas. Success of these activities relies upon knowledge and participation of various actors inside and outside the IT area, imposing challenges not observed in internally developed systems. This paper proposes a model for the analysis of ERP systems management based on a previous work on the subject with the inclusion of the IT capabilities model and a description of the actors (stakeholders) involved in the process of using an ERP system in a company. The proposed model is the basis for an exploratory survey conducted with 85 Brazilian companies whose results also comprise this text. The results suggest that only part of the capabilities is present and only part of the actors effectively participates on the ERP systems management effort.